Smart RFID library system - An, Yang (2012)
Radio frequency identification (RFID) is the use of a wireless non-contact system which adopts radio-frequency electromagnetic fields to transfer data in between a reader and a tag attached to an object, for the purposes of automatic identification or tracking. So far this RFID technology is used in many industry areas such as hospital, car park, warehouse, and zoo and so on. In this report, we try to replace the conventional barcode type library system with a new smart library system based on the RFID technology. In this RFID system, people just need to carry the books and stand close to the system’s antenna, all the books can be easily detected and after that people can do the further processing like borrow, return or check out information. Compare to the conventional barcode system. Some advantages are very obvious and valuable, for example, (i) Saving people’s time, whether the person is patron or librarian. Books can be scanned at one time and that is always faster than the scan one time by one time. (ii) Easily tracking. By attaching the RFID tag, the books can be detected and tracked wirelessly by the antenna. So after the communication between tag and reader, the system can quickly find out where is the exact location which the book staying. So with this function, the user can easily find out the book’s location. (iii) Wirelessly. The traditional barcode technology need direct line of sight to complete the scan process. That is troublesome and time consuming. RFID reader can make the communication without line of sight to the either active RFID tags or passive RFID tags. It is very convenience. (iv) The range of detection for RFID is much larger than barcode. Normally the valid working distance for RFID is up to 300 feet but only 15 feet for barcode. (v) Barcode does not have the read/write capability. You only can read the information out but cannot write anything in. However, this read/write function is installed inside RFID devices. The RFID reader can “talk” to the tag and amend as much of the information as the tag designed to allow.